Lift and Drag Performances of O-Ring Paper Plane - I. Ismail, N.; Yusoff, Hamid; Sharudin, Hazim; Pahmi, Arif; Suhaimi, S.; Rahman Hemdi, Abdul (International Journal of Engineering and Technology, 2018)
The O-ring paper plane is viewed as another option of paper planes that have potential to be upgraded as Micro Air Vehicle (MAV). Despite the complexity of the closed wing design, the O-Ring (OR) paper planes are easy to develop by following a certain origami technique. However, the aerodynamics performances for such closed wing design is still open to be explored before it can be upgraded for MAV usage. The aerodynamics complexity of closed wing design combined with various hoop sizing may induced complicated aerodynamics performance for OR paper planes. Thus, the objective of this research is to investigate the hoop diameters influence towards the aerodynamics performance of OR paper plane. Three different OR paper planes configurations known as OR-1, OR-2 and OR-3 have been used for comparative study. ANSYS-CFX simulation was fully utilized in this works to simulate the virtual wind tunnel on each OR paper planes configurations. Â The comparison works have been conducted to study the distributions of CL, CD and CL/CD on the closed wing configurations. CL results shows that OR-3 induces 16.6% better CL magnitude compared to OR-2 and OR-1. In fact, the OR-3 and OR-2 with larger hoop size produced better CLmax and Î±stall performances compared to smaller hoop configuration (OR-1). The CD performance also shows that OR-3 (with larger hoop configuration) produced at least 1.4% better CD min than the other configurations. However, the results show that OR-3 configurations has suffered from larger CD increment with at least 2% larger CD increment magnitude compared to OR-2 and OR-1. CL/CDmax results exhibited that OR-3 induces the highest CL/CDmax at 6.27 which is about 5.9% and 13.1% higher than OR-2 and OR-1 produced, respectively. The analysis on the low-pressure distribution area reveals that larger area of low pressure CP found on OR-3 has been lead into better CL magnitude for OR-3. Based on these results, one can presume that larger hoop size on OR paper planes induces higher CL and CL/CD max performances due to better low-pressure CP distributions on the wing.Â Â